Novel, human cell line‐derived recombinant factor VIII (Human‐cl rhFVIII, Nuwiq®) in children with severe haemophilia A: efficacy, safety and pharmacokinetics. (14th September 2015) - Klukowska, A.; Szczepański, T.; Vdovin, V.; Knaub, S.; Jansen, M.; Liesner, R.
Abstract : Introduction: Nuwiq ® (Human‐cl rhFVIII) is a new‐generation recombinant factor VIII (rFVIII) protein, without chemical modification or fusion to any other protein, produced in a human cell line. Aim/Methods: This prospective, open‐label, multinational phase III study assessed the efficacy and safety of Human‐cl rhFVIII in 59 previously treated patients (PTPs) with severe haemophilia A aged 2–12 years (2–5 [ N = 29]; 6–12 [ N = 30]) during standard prophylaxis (≥50 exposure days and ≥6 months). Efficacy in treating breakthrough bleeds and during surgical prophylaxis was also assessed. Results: An initial pharmacokinetic assessment ( N = 13 per age subgroup) demonstrated comparable results with the one‐stage and chromogenic assays. Mean (SD) half‐life was 11.9 (5.4) and 13.1 (2.6) hours in children aged 2–5 years and 6–12 years respectively (one‐stage assay). Prophylactic efficacy, based on mean monthly bleeding rate, was 'excellent' or 'good' in 91.5% of children for all bleeds and in 96.6% of children for spontaneous bleeds. Mean (SD) annualized bleeding rate was 4.12 (5.22) [median 1.9] for all bleeds, 1.50 (3.32) [median 0] for spontaneous bleeds and 2.34 (3.54) [median 1.57] for traumatic bleeds. There were no major, life‐threatening bleeds. Efficacy was 'excellent' or 'good' in the treatment of 82.4% of breakthrough bleeds. Overall efficacy during five major surgeries was rated as 'excellent'. There were no FVIII inhibitors or treatment‐related serious adverse events. Conclusion: These results in paediatric PTPs indicate that Human‐cl rhFVIII is effective for the prevention and treatment of bleeds.